2006
DOI: 10.1029/2005ja011339
|View full text |Cite
|
Sign up to set email alerts
|

Striated drifting auroral kilometric radiation bursts: Possible stimulation by upward traveling EMIC waves

Abstract: [1] We investigate waves observed by the Cluster wideband instrument (WBD) during an orbital conjunction with the Polar spacecraft. During this perigee pass, Polar was at the upper extent of the auroral kilometric radiation (AKR) source region in the Southern Hemisphere nightside auroral region. Cluster was located at higher altitude above this region and observed AKR with clear signatures of ordered fine structure striations (rain). Using electron particle data observed by HYDRA on board Polar, we have modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…This modulation is a function of electron energy and frequency (Figures 8 and 9) and should propagate along the magnetic field line at the group velocity of the EMIC waves producing a frequency‐drifting signature [cf. Menietti et al , 2006]. Growth of AKR will be strongest in a small range of frequencies near local f ce along the magnetic field line.…”
Section: Discussionmentioning
confidence: 99%
“…This modulation is a function of electron energy and frequency (Figures 8 and 9) and should propagate along the magnetic field line at the group velocity of the EMIC waves producing a frequency‐drifting signature [cf. Menietti et al , 2006]. Growth of AKR will be strongest in a small range of frequencies near local f ce along the magnetic field line.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary structures have recently been suggested as the cause of frequency fine structure seen in dynamical spectra of AKR radiation [ Pottelette et al , 2001, 2003; Pottelette and Treumann , 2005; Mutel et al , 2006]. We also briefly consider the effect of electromagnetic ion cyclotron (EMIC) waves, which have been associated with stimulation of AKR [ Menietti et al , 2006; Xin and Menietti , 2007].…”
Section: Growth Rate Modification Caused By Solitary Structures and Ementioning
confidence: 99%
“…Gurnett and Anderson [1981] first suggested that the drifting narrowband features were the result of a propagating disturbance which triggers narrowband AKR emission at the local cyclotron frequency. Several recent papers ascribe AKR fine structure to solitary structures such as electron holes [ Pottelette et al , 2003], ion holes [ Mutel et al , 2006], tripolar structures [ Pottelette and Treumann , 2005], or to electromagnetic ion cyclotron waves [ Menietti et al , 2006; Xin and Menietti , 2007]. These waves propagate along (or obliquely to) field lines and are thought to modify the electron distribution so as to enhance the CMI growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Pottelette et al (2001) presented a theory based on electron holes to explain typical or random fine structure of AKR. Menietti et al (2006) pointed out that electrons holes are more abundantly observed in downward current regions, so they would be less likely to be responsible for generating AKR emissions, which is thought to be produced in upward fieldaligned current regions. Mutel et al (2006) proposed that ion holes, rather than electron holes or tripolar structures, are the source of AKR ordered fine structure.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%
“…Mutel et al (2006) proposed that ion holes, rather than electron holes or tripolar structures, are the source of AKR ordered fine structure. Analyzing Cluster WBD observations of ordered AKR fine structure and electron distributions taken by the Polar HYDRA instrument near magnetic conjunction, Menietti et al (2006) found that the unstable electron horseshoe distributions in/near the AKR source region can also produce electromagnetic ion cyclotron (EMIC) waves. They proposed that ordered AKR fine structures can be stimulated by upward propagating EMIC waves.…”
Section: Betatron and Stochastic Accelerationmentioning
confidence: 99%